Flexible bacterial cellulose-based BC-SiO2-TiO2-Ag membranes with self-cleaning, photocatalytic, antibacterial and UV-shielding properties as a potential multifunctional material for combating infections and environmental applications - Rahman, Kifayat U.; Ferreira-Neto, Elias P. [UNESP]; Rahman, Ghaws U.; Parveen, Rashida; Monteiro, Andreia S. [UNESP]; Rahman, Gul; Van Le, Quyet; Domeneguetti, Rafael R. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Ullah, Sajjad [UNESP] (My University, 2021)
This research study reports the formation of flexible and multifunctional organic-inorganic hybrid membranes (BC-SiO2-TiO2/Ag) based on bacterial cellulose (BC) that contain photoactive (TiO2) and antibacterial (Ag) components, rendering them photocatalytic, self-cleaning and UV-shielding properties (due to TiO2) as well as antibacterial activity. Coating of BC with sol-gel derived silica and titania particles was achieved through hydrolysis-polycondensation of tetraethyl orthosilicate and titanium (IV) isopropoxide, respectively, and a soft hydrothermal treatment (140 °C, 20 h) was used to obtain well-crystalline TiO2. The prepared BC-SiO2-TiO2/Ag photoactive membranes were characterized by an array of analytical techniques including XRD, XRF, SEM-EDS, electronic absorption spectroscopy and vibrational spectroscopy. The morphology of TiO2 coatings changes from a homogenous film-like smooth one to a rougher one consisting of randomly oriented titania particles (170 ± 35 nm) upon increasing the TiO2 loading of the membranes. These prepared photoactive BC-SiO2-TiO2 membranes exhibited excellent TiO2-loading dependent photocatalytic/self-cleaning activity towards crystal violet dye deposited as an over-layer on the surface of the membranes, degrading 97 % of the dye within 50 min of UV illumination. In addition to good photoactivity, the BC-SiO2-TiO2/Ag membranes demonstrated reasonable antibacterial activity against five different bacterial strains under dark conditions. These flexible BC-based hybrid membranes with photocatalytic, self-cleaning, antibacterial properties have the potential to be used in the design of self-cleaning and antibacterial surfaces, filters and facemasks that could be easily disinfected under UV irradiation from a lamp or natural sunlight and safely discarded and even recycled.
Keywords: Antibacterial; Bacterial cellulose; Photoactivity; Self-cleaning; Silver; TiO2